2014
DOI: 10.5194/acp-14-8483-2014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of external industrial sources on the regional and local SO<sub>2</sub> and O<sub>3</sub> levels of the Mexico megacity

Abstract: The air quality of megacities can be influenced by external emission sources on both global and regional scales. At the same time their outflow emissions can exert an impact to the surrounding environment. The present study evaluates an SO 2 peak observed on 24 March 2006 at the suburban supersite T1 and at ambient air quality monitoring stations located in the northern region of the Mexico City Metropolitan Area (MCMA) during the Megacity Initiative: Local and Global Research Observations (MILAGRO) field camp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Previous analysis of emissions from the Popocatépetl Volcano showed that the wind direction pointed northwest toward the MCMA for less than 20% of the analysis period [Grutter et al, 2008]. A previous analysis of SO 2 levels in the MCMA attributed a significant fraction of its emissions to local cement plants and industrial processes in the Tizayuca region [Almanza et al, 2014]. Other studies have demonstrated the impact of SO 2 emissions from the Tula Industrial Complex, located northwest of Mexico City [de Foy et al, 2007;Karydis et al, 2011;Ying et al, 2014].…”
Section: 1002/2017jd026739mentioning
confidence: 97%
“…Previous analysis of emissions from the Popocatépetl Volcano showed that the wind direction pointed northwest toward the MCMA for less than 20% of the analysis period [Grutter et al, 2008]. A previous analysis of SO 2 levels in the MCMA attributed a significant fraction of its emissions to local cement plants and industrial processes in the Tizayuca region [Almanza et al, 2014]. Other studies have demonstrated the impact of SO 2 emissions from the Tula Industrial Complex, located northwest of Mexico City [de Foy et al, 2007;Karydis et al, 2011;Ying et al, 2014].…”
Section: 1002/2017jd026739mentioning
confidence: 97%
“…In this work, we also considered other lower rates (30 and ____________________________________________________________________________ 2019 / 23 23 50 g s −1 ). The maximum emission rate was determined at 1000 g s −1 per km 2 , based on industrial emissions derived from mega cities such as Mexico [74].…”
Section: Design and Control Of The Tropospheric Sulfate Aerosol Emissmentioning
confidence: 99%
“…Se han presentado diferentes trabajos de modelización de calidad del aire para la zona centro de México (García-Reynoso et al 2009, Mena-Carrasco et al 2009, Song et al 2010, Jazcilevich et al 2011, Almanza et al 2014, García-Escalante et al 2014, Ruiz-Suárez 2015 y para toda la República Mexicana (Tie et al 2007, Emmons et al 2010. En el desarrollo de dichas investigaciones se han empleado inventarios de emisiones.…”
Section: Introductionunclassified